Innovation and Information Technology in Services - Georg Licht; Dietmar Moch (Zentrum für Europäische Wirtschaftsforschung (ZEW), 1997)
The missing effect of investments of firms in information and communication technologies on productivity is studied by various recent papers (e.g. Oliner and Sichels 1994, Landauer 1995, Brynjolfsson and Hitt 1996). Several explanations are given for this missing link. Our paper deals with two of them, using two newly available data sets for the German service sector. Using data from a survey of innovative activities in services we show that investment in information technology (IT) has a stronger effect on the quality of services than on the productivity of the IT-using firm. IT investment seems to be especially effective when innovations enhance the delivery speed and the spatial or temporal availability of service. Moreover, data of the German IT survey point towards the need to differentiate between types of IT investment. It is shown that especially the most recent generation of IT as indicated by the number of PCs used is the source of productivity growth whereas traditional IT like mainframes exhibit only minor productivity effects. We conclude from our results that mismeasurement of the quality of new products and processes is one important reason for our inability to uncover the productivity effect of IT. Moreover, dividing IT-investment by the type of IT clarifies that the kind of IT a firm uses is more important for productivity growth what than its quantity. In any case we expect that the bulk of the IT-related productivity growth is still to come. In order to realize the benefits from IT investment entirely, firms have to undergo a large restructuring of business functions.
Keywords: O33; D24; L80; 330; Information Technology; Productivity; Service Sector; Dienstleistungssektor; Informationstechnik; Computergestütztes Verfahren; Produktivität; Innovation; Dienstleistungsqualität; Schätzung; Deutschland